mmWave Compound Link Budget Model of Dust and Humidity Effect - Hayder R. Idan; Basim K AL-Shammari; Hasan F. Khazal (Wasit Journal of Engineering Sciences)
mmWave Path Loss (PL) Link Budget (LB) modeling considerations are based on many different factors. For instance, the third generation partnership project (3GPP) model is mainly based on the distance from an Access Point (AP) and the frequency of transmission as well as the transmission link budget situation. Furthermore, there are certain interesting models about the effects of dust and humidity on the mmWave propagation. These models had introduced the consequences of the humid and dusty environments without consideration for the additional mmWave transmission LB parameters. First of all, this paper introduces an average dust and humidity model based on statistical Z-test in order to overcome the variation in the results between the three chosen models for dust and humidity effect in the mmWave range. Secondly, it proposes LB compound model, that comprises 3GPP PL LB with an average dust and humidity model. This introduced compound model has been applied on RMa PL LB with and without the presence of dust and humidity. The simulation of the presented model has been applied for distinct distances from the AP and mmWave transmission frequency range from 0.5 to 30 GHz.